Do clinical guidelines reduce clinician dependent costs? - English Mike; Hanson Kara; Kosimbei George (BMC, 2011)
Abstract Clinician dependent costs are the costs of care that are under the discretion of the healthcare provider. These costs include the costs of drugs, tests and investigations, and discretionary outpatient visits and impatient stays. The purpose of this review was to summarize recent evidence, relevant to both developed and developing countries on whether evidence based clinical guidelines can change hospitals variable costs which are clinician dependent, and the degree of financial savings achieved at hospital level. Potential studies for inclusion were identified using structured searches of Econlit, J-Stor, and Pubmed databases. Two reviewers independently evaluated retrieved studies for inclusion. The methodological quality of the selected articles was assessed using the Oxford Centre for Evidence- Based Medicine (CEBM) levels of evidence. The results suggest that 10 of the 11 interventions were successful reducing financial costs. Most of the interventions, either in modeling studies or real interventions generate significant financial saving, although the former reported higher savings because the studies assumed 100 percent compliance.